2020
DOI: 10.1007/s12253-020-00861-9
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 4 (SFRP4) Is an Independent Prognostic Marker in Prostate Cancers Lacking TMPRSS2: ERG Fusions

Abstract: Secreted frizzled-related protein 4 (SFRP4) controls WNT signaling and is thought to play a role for tumor aggressiveness. Here, we analyzed a tissue microarray containing 11,152 prostate cancers with pathological, clinical and molecular data by immunohistochemistry. SFRP4 expression was higher in cancer than in non-neoplastic acinar cells. SFRP4 staining was seen in 64.9% of tumors and classified as weak in 33.2%, moderate in 23.9% and strong in 7.8% of cancers. SFRP4 overexpression was linked to advanced tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…11 While there is evidence for an increase in sFRP4 expression in various cancers, some studies have shown a decrease. [39][40][41] In our study, sFRP4 levels did not differ in CRC patients compared to healthy individuals, this may be due to the limited number of patients. It is important to note the discrepancies in findings and further research is required to fully understand the role of sFRP4 in cancer.…”
Section: Discussioncontrasting
confidence: 54%
“…11 While there is evidence for an increase in sFRP4 expression in various cancers, some studies have shown a decrease. [39][40][41] In our study, sFRP4 levels did not differ in CRC patients compared to healthy individuals, this may be due to the limited number of patients. It is important to note the discrepancies in findings and further research is required to fully understand the role of sFRP4 in cancer.…”
Section: Discussioncontrasting
confidence: 54%
“…The SFRP4 protein is a suggested tumor suppressor thought to inhibit Wnt-signaling by hindering the extracellular Wnt-ligand to attach to the receptor 5 . However, we and others have identi ed increased SFRP4 gene expression with increasing prostate cancer aggressiveness [6][7][8][9] , which also have been found for several other cancers 10 . In the context of personalized medicine, SFRP4 gene expression has the potential to improve diagnosis and prognosis accuracy.…”
Section: Introductionsupporting
confidence: 61%
“…SFRP4 overexpression in both androgen-dependent and androgen-independent cell lines resulted in a morphologic change to a more epithelioid cell type with increased localization of b-catenin and cadherins (Ecadherin in LNCaP, N-cadherin in PC3) to the cell membrane (38). Previous studies showed that SFRP4 overexpression was linked to advanced tumor stage, high classical/quantitative Gleason grade (p < 0.0001 each), lymph node metastasis (p = 0.0002), and a positive surgical margin (p = 0.0017), and SFRP4 expression was an independent predictor of recurrence after prostatectomy (HR = 1.35; p = 0.009) (22,37). In addition, SPP1 is a cardinal mediator of tumor-associated inflammation and facilitates metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we firstly developed and confirmed that EMTGPI could predict BCR probability and drug resistance effectively for PCa patients undergoing radical prostatectomy or radiotherapy. SFRP4 controls WNT signaling and is thought to play a role for tumor aggressiveness ( 37 ). SFRP4 overexpression in both androgen-dependent and androgen-independent cell lines resulted in a morphologic change to a more epithelioid cell type with increased localization of β-catenin and cadherins (E-cadherin in LNCaP, N-cadherin in PC3) to the cell membrane ( 38 ).…”
Section: Discussionmentioning
confidence: 99%